PENGARUH KREATIVITAS GURU TERHADAP MINAT BELAJAR SISWA DI SMK NEGERI 26 JAKARTA - Nadiah; Bima Satyadinata (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
The role of creativity from a teacher is an important thing that needs to be considered byteachers in creating learning to be more effective and optimal. The purpose of this study isto determine whether or not there is an influence of teacher creativity on student learninginterest in SMK Negeri 26 Jakarta. The method used in this study is descriptivecorrelational analytics. The analysis technique used is the Product Moment coefficient.The results of the data obtained at the product moment about the influence of teachercreativity on student learning interest at SMK Negeri 26 Jakarta amounted to 0.432%. Itis proven that with a statistically significant calculation of 5% with a df of 0.361, Ho wasrejected and Ha was accepted, meaning that there was an influence of teacher creativityon student learning interest at SMK Negeri 26 Jakarta. From the results of the determinant(Rsquare) it was concluded that the influence of variable (X) teacher creativity on variable(Y) student learning interest was 43.2% and as much as 81.6% was influenced by otherfactors not studied by the author.